Etika Berkomunikasi Dalam Presfektif Hadis - Syawal Kurnia Putra; Erwin Hafid; Arifuddin Ahmad (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study is to describe and analyze the ethical principles of communication described in the hadiths of the Prophet. This research is library research using qualitative descriptive methods, data sources are through journals, books related to communication ethics. Data analysis used interactive qualitative analysis according to Miles and Huberman. The results of the study show that in speaking you should use good and polite words; speak effectively and efficiently so as not to take up much time; speak based on facts and reality and stay away from lies; when speaking, invite people who are older and have a higher level of understanding and knowledge; not speak that hurts and puts other people in a corner; stay away from debates in order to avoid problems; Communication that is carried out to convey information or messages to the communicant must be positive and useful and in accordance with what has been exemplified by the Prophet